Knocking at the gate: The path to publication for entrepreneurship experiments through the lens of gatekeeping theory - Stevenson, Regan M.; Josefy, Matthew (Journal of Business Venturing, 2019)
We draw on gatekeeping theory to explore the individual and routine-level criticisms that entrepreneurship experimentalists receive during the review process. Using a multi-study approach, we categorize common gatekeeping themes and present illustrative critiques derived from a unique sample of decision letters and a supplemental survey of entrepreneurship editors. In combination, we extend gatekeeping theory by considering how it applies to the scholarly domain, contribute to the literature by exploring an alternative theoretical explanation as to why entrepreneurship experiments might fail to survive the review process, and finally, provide contextualized recommendations for authors and reviewers of experimental research.